Lexicography, translation and terminology: relationships derived from Della Geometria di Orontio Fineo tradotte da Cosimo Bartoli (Venetia, 1587) - Sánchez Martín, Francisco Javier (MonTi Monografías de Traducción e Interpretación, 2015)
The mathematical books composed by the French mathematician Oronce Finé gained a great prestige in the sixteenth century, as evidenced by the translations of his work about Geometry, Optics, Geography and Astronomy, Protomathesis: Opus varium. Now, our interest is focused on Della Geometria, the second book of Opere di Orontio Fineo del Delfinato, divise in cinque parti, translated by Cosimo Bartoli (Venetia, Francesco Franceschi Senese, 1587). We carry out a terminological study to compare both works, the source text and this Italian translation. This analysis allows us to examine the processes of lexical convergence which are characteristic in this lexicon of Greco- Roman origin, on the one hand, and to study the formal and the semantic neologisms in this specific field, on the other. Finally, we will verify the use of the same mechanisms to disseminate this technical vocabulary, both in Latin and Italian.